Review to Viola, Lorella. The Humanities in the Digital: Beyond Critical Digital Humanities. Palgrave Macmillan, 2023 - , Z. CANSU RENDECI (2024)
Lorella Viola's The Humanities in the Digital: Beyond Critical Digital Humanities advocates for a paradigm shift in how knowledge is created and shared in the digital age. Published as an open-access volume, the book challenges traditional divisions and offers a novel framework for digital scholarship. The book introduces the post-authentic framework, emphasizing the need to move beyond traditional divisions, such as digital versus non-digital, and critiques existing positivistic approaches to digital tools. Viola argues that digital tools are not neutral and require critical human intervention at every stage to ensure ethical and transparent knowledge production. Despite offering valuable theoretical insights, the book focuses more on critique than practical applications, suggesting the need for future research to bridge theory with real-world digital humanities practices.